A multivariate evaluation of environmental effects on zooplankton community structure in the western North Atlantic. (May 2015) - Pepin, Pierre; Johnson, Catherine L.; Harvey, Michel; Casault, Benoit; Chassé, Joël; Colbourne, Eugene B.; Galbraith, Peter S.; Hebert, Dave; Lazin, Gordana; Maillet, Gary; Plourde, Stéphane; Starr, Michel
Highlights: We investigated variations in zooplankton community structure in the NW Atlantic. Bathymetry, surface temperature and salinity are primary biogeographic drivers. Deep water intrusions and vertical habitat availability influence taxonomic diversity. Mesoscale circulation features may shape communities within each major LME. A few key taxa dominated the delineation of communities in both spring and fall. Abstract: We report on our analysis of zooplankton community structure in the western North Atlantic based on spring and fall monitoring surveys from 1999 to 2011 of three large marine ecosystems (LMEs; Newfoundland Shelf, Gulf of St. Lawrence and Scotian Shelf). We aimed to synthesize knowledge of the distribution of zooplankton communities and to evaluate their relationship to environmental conditions as either biogeographic constraints or smaller-scale ecosystems drivers or both. A combination of exploratory and constrained analyses helped identify the dominant roles of bathymetry, surface salinity and temperature, subsurface biogeochemical inventories of nitrate and chlorophyll a on the macroscale distribution of zooplankton. These variables highlight the potential influences of vertical habitat features, latitudinal and estuary–ocean gradients, deep-water intrusions, and differences in the seasonal succession on community structure at biogeographic scales. The spatial pattern in the residual field of the constrained analysis suggests that mesoscale features may play a role in shaping community structure within each of the LMEs and point to the limitation of analytical approaches based principally on water mass tracers applied over broad-scales. Interannual variations in key environmental drivers had inconsistent abilities in predicting changes in community composition across LMEs. Organisms that had the greatest influence on the delineation of communities were similar between spring and fall surveys and consisted of roughly a dozen dominant and ubiquitous taxa. Determining the influence of environmental variations on productivity of key secondary producers requires an approach focussed at the scale of individual LMEs in order to address the consequence of dissimilarities in the dominant trophic relationships or the response to remote forcing across the region.